Analisis Keselamatan Transportasi Pelayaran Rakyat - Malisan, Johny (Warta Penelitian Perhubungan, 2010)
Population of tradi.tional shipping tends to decrease due to numy accidents happen that should beanalyzed, particularly relating to technical and non-teclmical •cts which are suppofed to influence itssafehj perftmnance. The teclmical aspects to be revien~d include construction strength and stabilihj ofship. Mernwhile non-technical aspects to be revielwl are including qxrational management of ships onland and rompetence of crews. Another~ is safety management in order to realize "zero aaident"amrept. Metluxie for further analysis will ~ focused on study of literature in order to find tlreoretimlclarification and hypotheses related to those aspects affected to the snfehJ of traditional shipping asdescribed above.